Perilaku Pemborosan Pangan (Food Waste) oleh Rumah Tangga Petani di Kecamatan Teriak Kabupaten Bengkayang - Sabina Sabina; Maswadi Maswadi; Wanti Fitrianti (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Wasted food is a global issue that has been around for a long time but has become increasingly serious without realizing it. The resulting impacts negatively affect many sectors, such as the environment, economy and social. Food waste can reduce farmers' income and increase consumer spending. Households can be said to be the biggest contributors to food waste because apart from daily consumption activities, the most dominant livelihood system of the people in Teriak sub-district is farming. The characteristics of farming households that play a major role in meeting household food needs are the socio-economic conditions of farmers, because it can describe the capacity of farmers in meeting their food needs, research was conducted on the causes of food waste behavior by farming households, especially Teriak District. This research aims to determine household consumption behavior towards the emergence of food waste and identify the influence of socio-demographic and socio-economic factors on food waste behavior by households in Teriak District, Bengkayang Regency. The research method used in this research is descriptive statistics with 100 sample respondents representing households. The variables in this study are divided into two, namely socio-demographics and household behavior. The research results show that the behavior of farming households is influenced by socio-demographic and socio-economic characteristics of respondents such as age, length of education, number of family members, income and expenses. Food waste behavior includes several aspects such as the social environment, purchasing, storage, processing and consumption.